ChemInform Abstract: Synthesis of 1, 1‐Diboronate Esters by Cobalt‐Catalyzed Sequential Hydroboration of Terminal Alkynes. Issue 33 (July 2016) - Zuo, Ziqing; Huang, Zheng
Abstract: An efficient procedure for the Co‐catalyzed conversion of terminal alkyl and aryl alkynes with pinacolborane affording 1, 1‐diboronate esters is developed.